2004
DOI: 10.1021/jp049154h
|View full text |Cite
|
Sign up to set email alerts
|

A Full Dimensional Quasiclassical Trajectory Study of Cl + CH4 Rate Coefficients

Abstract: The Cl + CH4 reaction has been investigated using a full dimensional quasiclassical trajectory technique and a new potential energy surface. The new surface is generated by expanding the interaction in terms of minimum energy paths in the Bond Order space. Results are compared with those obtained on another recently proposed potential energy surface and with experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
14
1
Order By: Relevance
“…In fact, the QCT method has been widely used to study all kinds of dynamical problems for reaction systems involving three and four atoms [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] over the decades and is becoming popular in studying the reaction dynamics of larger systems. [44][45][46][47][48][49] In the present work, we performed detailed QCT calculations on the 12-dimensional ab initio WSB surface 22 for the SiH 4 +H→ SiH 3 +H 2 reaction. Various dynamical quantities are obtained and reaction mechanisms are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the QCT method has been widely used to study all kinds of dynamical problems for reaction systems involving three and four atoms [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] over the decades and is becoming popular in studying the reaction dynamics of larger systems. [44][45][46][47][48][49] In the present work, we performed detailed QCT calculations on the 12-dimensional ab initio WSB surface 22 for the SiH 4 +H→ SiH 3 +H 2 reaction. Various dynamical quantities are obtained and reaction mechanisms are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous theoretical studies of the Cl + CH 4 reaction and its reverse 5–30 . Duncan and Truong reported a direct ab initio dynamics study of thermal and vibrationally state‐selected rates of this reaction 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on a vibrationally diabatic model, they concluded that there is a significant enhancement in reaction rate when the CH 4 symmetric stretching mode is excited, which is subsequently confirmed by a recent experiment 31 . Several other potential energy surfaces (PESs) have been produced, 7–14 and used in quasiclassical trajectory studies (QCT) 11,14–17 and reduced dimensionality quantum dynamics calculations 8,9,18–21 . In addition, there have been direct dynamics calculations on this system 22,23 and numerous calculations based on variational transition state theory 6,7,10,14,24,25,27,29,30 …”
Section: Introductionmentioning
confidence: 99%
“…The dynamical full‐dimensional quasi‐classical calculations performed on the MEP–MPE PES indicate that the cone of acceptance is too large. As a matter of fact, the room temperature rate coefficient was estimated to be 29 2.07 ± 0.18 × 10 −13 cm 3 molecule −1 s −1 , a value twice as large as the IUPAC recommended one that is 1.0 cm 3 molecule −1 s −1 30.…”
Section: Properties Of the Mep–mpe Pesmentioning
confidence: 92%